(untitled) (Journal of Engineering, 2006)
In this research a modern scientific procedure was used utilizing geographic information system GIS in selecting the optimum road path between two cities . All the programming facilities offered by ArcView GIS software with its extensions of spatial analysis and 3D analysis to solve the problem .The solution take a form of geographic map graduated in colors from best to bad portion of land that the suggested road could pass through. The proposed procedure was checked by conventional mathematical solution used in such problems and the results were both agreed.